Association of self-reported snoring with decreased retinal thickness and vessel density - Xiao, Yunfan; Shi, Keai; Li, Chunmei; Yang, Kai; Zhu, Xiaoxuan; Su, Binbin; Ju, Ying; Lu, Fan; Qu, Jia; Li, Ming; Cui, Lele (Frontiers in Physiology, 2022)
Abstract Purpose: Self-reported snoring has been reported to influence nerves and vessels. However, there are few direct evidences of snoring related to nerves and microvessels defects. Therefore, we evaluated the association of self-reported snoring with retinal structure and microcirculation. Methods: A total of 2622 participants were recruited from the Jidong eye cohort study (JECS). Physical examinations, laboratory tests, and questionnaires were recorded. We also used optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) to assess the retinal structure and microvascular network. Snoring was defined as “never”, “occasionally”, and “frequently or more severe” according to self-reported frequency. Results: The prevalence of snoring were 84.6% (n = 983) and 45.0% (n = 657) in males and females, respectively. Compared with never snoring group, the retinal thickness increased in “occasionally” (p＜0.001) and “frequently or more severe” groups (p = 0.001), while insignificance different was found between these two groups (p = 0.14). superficial retinal capillary plexus (RCP) vessel density was lower in “frequently or more severe” group than in “never” (p<0.001) and “occasionally” snoring groups (p<0.001). After adjusting for confounders, “frequently or more severe” snoring was significantly associated with thinner total retinal thickness (β = -2.79 [95% CI: -5.27, -0.30]) and lower superficial RCP vessel density (β = -0.71 [95% CI: -1.19, -0.23]). Conclusions: Our research showed self-reported snoring was associated with thinner retinal thickness and lower superficial RCP vessel density. The findings of our study emphasize the need for self-reported snoring assessments in determining retinal structure and microcirculation impairment.